Academic burnout among trainee teachers during the COVID-19 pandemic: Effect of sociodemographic factors - Abdelmounaim Bouhaba; Youssef El Madhi; Abdelmajid Soulaymani; Hinde Hami (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The trainee teacher seems to be more and more faced with frustration and stress during the training phase, caused by accumulation of requirements and duties, making them susceptible to the risk of burnout. The purpose of this work is to study the academic burnout of trainee teachers at the Rabat-Sale-Kenitra region's Regional Center for Education and Training Professions during the COVID-19 pandemic. MATERIALS AND METHODS: Seven hundred thirty-nine trainee teachers responded to a self-questionnaire comprising the Maslach Burnout Inventory-Student Survey scale in its French validated version, as well as stress factors during the academic year 2020-2021. Both inferential and descriptive methods of data analysis were used to represent the effect of sociodemographic variables on burnout levels during the COVID-19 pandemic. RESULTS: In agreement with the literature, most of trainee teachers show moderate and high levels of academic exhaustion; the main stressors presented are financial instability and training overload, and the level of study influences the scale of burnout among trainee teachers. CONCLUSION: The result of this study can serve as a predictor of academic burnout among Moroccan trainee teachers.